Desenvolvimento de um aditivo probiótico utilizando bactérias ácido lácticas autóctones do trato gastrointestinal de patos crioulo (Cairina moschata domesticus L., 1758) - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Domestic ducks are birds that adapt to the different climatic conditions in Brazil and their breeding is expanding, mainly due to their ease of management. In Amazonas, it is raised mainly in the semi-extensive or free-pasture system, in which the animals are enclosed in closed sheds at night to protect against predation. They reach slaughter age at 90 days, therefore, they are slow-growing birds. In poultry farming, the need for alternative products is evident, which can be used to promote the productive performance of birds, improving feed conversion, carcass yield and animal health, among which the use of microorganisms with probiotic potential stands out. The aim of the present study was to investigate the effects of different autochthonous lactic acid bacteria as probiotic additives for housed landrace ducks on performance, carcass characteristics and serum biochemical parameters. Domestic ducks (n = 96) of the Creole lineage were arranged in a completely randomized design, where the treatments consisted of a control (without the use of probiotic) and three strains of autochthonous lactic acid bacteria as probiotic administered to the birds (Enterococcus lactis, E. ratti and E. faecium), with three replications of eight birds each. The collected data were subjected to the Tukey test at 0.05. During the initial phase, no significant impact (p>0.05) on feed consumption and weight gain was observed, however feed efficiency was significantly affected (p<0.05), where the control group showed better results. Likewise, during the growing and finishing phases, varied results were obtained in relation to feed consumption, weight gain and feed efficiency, suggesting that the effectiveness of probiotics may be influenced by the specific strain and environmental conditions, but presenting results lower (p<0.05) than those obtained in the control group. Notably, certain probiotic strains, such as E. lactis, showed promise in increasing (p<0.05) feed efficiency and carcass characteristics (p<0.05), while others, such as E. faecium, exhibited effects significant (p<0.05) in all serum biochemical parameters. In conclusion, the inoculations of indigenous lactic acid bacteria in creole ducks showed varying effects on feed efficiency throughout the growth phases, influenced by strain. Specific strains improved feeding and carcass characteristics, emphasizing the importance of their selections.
Keywords: .; .; .; CIENCIAS BIOLOGICAS: MICROBIOLOGIA: BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS: BACTEROLOGIA; Enterococcus lactis; Enterococcus ratti; Enterococcus faecium; Eficiência alimentar